Plan de control de ruido y material particulado en el Grupo Empresarial C.I. S.A.S. (2023)
This degree project focuses on the development of a noise and particulate matter control plan in the company Grupo Empresarial C.I. S.A.S, whose main economic activity is the extraction and transformation of coal. These two processes generate a negative environmental impact directly in the air, such as the emission of noise and particulate matter, and cause possible negative impacts on the health of workers and nearby communities. It also seeks to identify all emission sources within the coal mine and the coking plant, which allows an analysis of those that have a high risk of contamination or those that have levels very close to the limits established in resolutions Number 627 of April 7, 2006 and 2254 of November 1, 2017. And thus, establish preventive and corrective measures that allow mitigating environmental problems within the company.